2019
DOI: 10.1155/2019/7362875
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Regulation of Melanoma Cell Death via Activation of Thermo-TRPV4 and TRPV2

Abstract: Background. Thermo-TRPs (temperature-sensitive transient receptor potential channels) belong to the TRP (transient receptor potential) channel superfamily. Emerging evidence implied that thermo-TRPs have been involved in regulation of cell fate in certain tumors. However, their distribution profiles and roles in melanoma remain incompletely understood. Methods. Western blot and digital PCR approaches were performed to identify the distribution profiles of six thermo-TRPs. MTT assessment was employed to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
(32 reference statements)
0
24
0
1
Order By: Relevance
“…DTL is involved with the regulation of cell cycles and playing a role in the regulation of DNA damage, so we suggest hat it regulate cycle of melanocytes so that to regulate its progression. TRPV2 is an ion channel, it's activation mediated melanoma cell death (Zheng et al, 2019), which may play a negative role in melanoma development. PLOD3 was found to be highly expressed in lung cancer and gliomas (Tsai et al, 2018), which is associated with poor prognosis of them.…”
Section: Discussionmentioning
confidence: 99%
“…DTL is involved with the regulation of cell cycles and playing a role in the regulation of DNA damage, so we suggest hat it regulate cycle of melanocytes so that to regulate its progression. TRPV2 is an ion channel, it's activation mediated melanoma cell death (Zheng et al, 2019), which may play a negative role in melanoma development. PLOD3 was found to be highly expressed in lung cancer and gliomas (Tsai et al, 2018), which is associated with poor prognosis of them.…”
Section: Discussionmentioning
confidence: 99%
“…These previous studies showed that TRPV4 activation caused severe cellular disarrangement, necrosis and apoptosis in melanoma. The experiments suggested that TRPV4 channel activation contributed to melanoma cell death via Ca ++ -influx, which also activated the AKT pathway with net anti-proliferative effects (49). One possible translational application is to enhance melanoma cell death via use of targeted UVB and/or topical TRPV4 agonists in conjunction with currently established melanoma treatments.…”
Section: Discussionmentioning
confidence: 99%
“…DTL is involved with the regulation of cell cycles and playing a role in the regulation of DNA damage, so we suggest hat it regulate cycle of melanocytes so that to regulate its progression. TRPV2 is an ion channel, it's activation mediated melanoma cell death [23] , which may play a negative role in melanoma development. PLOD3 was found to be highly expressed in lung cancer and gliomas [24] , which is associated with poor prognosis of them.…”
Section: Discussionmentioning
confidence: 99%